2012
DOI: 10.1111/j.1537-2995.2012.03734.x
|View full text |Cite
|
Sign up to set email alerts
|

Compound heterozygosity of HLA‐DRB3*01:01 and HLA‐DRB4*01:01 as a potential predictor of fetal neonatal alloimmune thrombocytopenia

Abstract: Overall, we suggest that a specific genotyping of the mother in relation to HLA-DRB as well as HPA-1 can serve as an antenatal diagnostic tool, particularly in siblings of women who gave birth to neonates with FNAIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 29 publications
1
34
1
Order By: Relevance
“…Furthermore, HLA‐DQB1*02:01 was overrepresented in anti‐HPA‐1a–alloimmunized women probably because of linkage disequilibrium with HLA‐DRB3*01:01 . Recently, Loewenthal and coworkers showed that HLA‐DRB4*01:01P also binds the HPA‐1a epitope leading to an immune response. Nevertheless, the model of HLA‐DRB4*01:01P crystal structure published by the authors shows that the binding cavity of this variant is less hydrophobic than that of HLA‐DRB3*01:01.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, HLA‐DQB1*02:01 was overrepresented in anti‐HPA‐1a–alloimmunized women probably because of linkage disequilibrium with HLA‐DRB3*01:01 . Recently, Loewenthal and coworkers showed that HLA‐DRB4*01:01P also binds the HPA‐1a epitope leading to an immune response. Nevertheless, the model of HLA‐DRB4*01:01P crystal structure published by the authors shows that the binding cavity of this variant is less hydrophobic than that of HLA‐DRB3*01:01.…”
Section: Discussionmentioning
confidence: 99%
“…In 90% of cases of HPA‐1a fetomaternal alloimmunizations, the mother carries this HLA Class II molecule . Recently, Loewenthal and colleagues suggested that HLA‐DRB4*01:01 also plays a role in HPA‐1a peptide presentation. They observed that the combination of both DRB3*01:01 and DRB4*01:01 antigens was associated with more severe cases of FNAIT and affects response to antenatal treatment with IVIG.…”
mentioning
confidence: 99%
“…HPA‐1a antibodies are the cause of the majority (~85%) of serologically confirmed FNAIT cases, in which a maternal platelet‐specific antibody is detected (Table ). Immunization to HPA‐1a is highly correlated with carrying the class II human leucocyte antigen (HLA), HLA‐DRB3*0101 , and more recently HLA‐DRB4*01:01 . The lower frequency HPA‐1b antigen is more commonly expressed in Caucasian populations, and individuals with the HPA‐1b/1b platelet type are those that can make HPA‐1a antibodies.…”
Section: Human Platelet Alloantigensmentioning
confidence: 99%
“…116,159,160 The most plausible explanation for this may be the strong association between the human leucocyte antigen (HLA) class II DRB3*0101 and DRB4*0101 alleles and HPA-1a alloantibody generation. 155 The DRB3 allele has also been demonstrated to have binding affinity for HPA-1a but not HPA-1b. 154 This implies that specific maternal antigen presentation pathway and a specific genetic background may be involved in fetal antigen alloimmunization.…”
Section: Mechanisms Of Alloantibody Generation In Fnaitmentioning
confidence: 99%